PELATIHAN MANAJEMEN KEUANGAN SEBAGAI UPAYA PENINGKATAN DAYA SAING UMKM PADA STUDIO FOTO IMAKO DI TRENGGALEK - ‘Aini, Yulis Nurul; Djajanto, Ludfi; Oktora, Yekie Senja; Lestari, Baroroh; Maskur, Maskur (Transpublika Publisher, 2024)
This activity aims to provide knowledge about financial management with the main topic being the preparation of operational budgets at Imako Trenggalek photo studio. The problems faced by partners are first, Imako has difficulty in preparing an operational budget to run a photo studio business due to lack of knowledge about financial management. Second, Imako has difficulty in sorting out business money and personal money. Third, the recording of expenditure and income transactions is unclear. Providing training and support to partners in making operational budgets and financial management is the solution offered.